2013
DOI: 10.1002/ls.1241
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation by in situ transmission electron microscopy of the behaviour of IF‐MoS2 nanoparticles during sliding tests: influence of the crystal structure

Abstract: Direct observation of the behaviour of individual inorganic fullerenes (IF)‐MoS2 nanoparticles in a sliding interface is essential for the understanding of the influence of the intrinsic characteristics of the nanoparticles on their lubrication mechanisms, when they are used as additives in lubricant oil. In this work, in situ transmission electron microscopy sliding tests were performed on two different types of MoS2 nanoparticles synthesised by two different methods. It is shown that the IF‐MoS2 nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…[4,35], the modified method was cheaper and the crystallization of MoS 2 was weaker because of the lower calcining temperature. The poor crystallization conduces to the friction reduction of nano-MoS 2 [36,37]. Thus, the modified method will not reduce the lubricating capability of nano-MoS 2 , which had been proved by tribological tests before this work.…”
Section: Ball-disk Friction Pairmentioning
confidence: 77%
“…[4,35], the modified method was cheaper and the crystallization of MoS 2 was weaker because of the lower calcining temperature. The poor crystallization conduces to the friction reduction of nano-MoS 2 [36,37]. Thus, the modified method will not reduce the lubricating capability of nano-MoS 2 , which had been proved by tribological tests before this work.…”
Section: Ball-disk Friction Pairmentioning
confidence: 77%
“…These mechanisms have since been observed by in situ transmission electron microscopy and scanning electron microscopy imaging [72,73] coupled with a nanoindentor/nanomanipulator and were shown to depend on the normal and shear stress as summarized in Fig. 11.…”
Section: Layered Nanomaterialsmentioning
confidence: 94%
“…However, it was found that the completely closed spherical structure did not present better lubrication than the partly closed one used in this work during the tests. The reason is that poorly crystallised spherical MoS 2 nanoparticles exfoliate very easily . Thus, the s‐MoS 2 prepared at a relatively low temperature (480°C) was selected as an additive in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Molybdenum disulfide (MoS 2 ) is a well-known layered solid lubricant with a hexagonal structure. MoS 2 has been widely applied as a lubricating additive in base oils, [1][2][3] greases, 4-6 plastics, 7,8 and coatings. 9,10 Thus, to improve the lubricating performance of MoS 2 is very important for industrial applications.…”
Section: Introductionmentioning
confidence: 99%